Investigation of Delamination Factor in High Speed Drilling on Chopped GFRP Using ANFIS. (2016) - Chaudhari, Ashish B.; Chaudhary, Vijay; Gohil, Piyush; Patel, Kundan
Abstract: High speed machining is a key method to increase the productivity and reduce the cost during manufacturing. Delamination is a prevalent disadvantage while drilling of composites. Full factorial design (FFD) was used to evaluate delamination factor (DF) by studying process parameters. DF was evaluated with an influence of process parameter during the drilling of composites such as, cutting speed, depth of cut and feed rate. For determination of significance of each process parameters analysis of variance (ANOVA) was studied with their influence on process parameters. Adoptive neuro fuzzy interface system (ANFIS) models were developed to predict delamination factor as a function of different combination of machining parameters. Comparison of experimental DF with the predicted ANFIS model was carried out. After comparing the experimental results with the predicted results it is found that the root means square error (RMS) at DF at entry and exit are1.4732% and 2.9277% respectively.